2009
DOI: 10.1016/j.jpsychires.2008.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Age-related gene expression in Tourette syndrome

Abstract: Because infection and immune responses have been implicated in the pathogenesis of Tourette Syndrome (TS), we hypothesized that children with TS would have altered gene expression in blood compared to controls. In addition, because TS symptoms in childhood vary with age, we tested whether gene expression changes that occur with age in TS differ from normal control children. Whole blood was obtained from 30 children and adolescents with TS and 28 healthy children and adolescents matched for age, race and gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 42 publications
0
37
0
Order By: Relevance
“…This finding might suggest an abnormal immune recognition of pathogens in TS patients, which might indirectly account also for an increased synthesis of cytokines in these patients. However, the age-dependent change in expression of immune regulatory proteins [24], although intriguing, was observed across different age strata within a cross-sectional analysis of a clinical sample of TS patients. Truly prospective observations are necessary to confirm this finding.…”
Section: Gene Expression Profiling Of Immune Cellsmentioning
confidence: 96%
See 1 more Smart Citation
“…This finding might suggest an abnormal immune recognition of pathogens in TS patients, which might indirectly account also for an increased synthesis of cytokines in these patients. However, the age-dependent change in expression of immune regulatory proteins [24], although intriguing, was observed across different age strata within a cross-sectional analysis of a clinical sample of TS patients. Truly prospective observations are necessary to confirm this finding.…”
Section: Gene Expression Profiling Of Immune Cellsmentioning
confidence: 96%
“…Fourteen NK cell genes were over-expressed in 10 of 16 familial cases of TS compared to 16 control subjects [23] using these methods. A subsequent study from the same group [24] on 28 case and 30 control children/adolescents found that the expression of a number of genes and multiple pathways differed between TS and control subjects within different age strata (5 to 9 years, 10 to 12 years, 13 to 16 years). Particularly, age-related expression changes specific of TS patients were observed for genes involved in viral response, including interferon processing and B cell immunoglobulin synthesis, and cell-mediated cytotoxicity mechanisms involving NK and CD8+ T cells.…”
Section: Gene Expression Profiling Of Immune Cellsmentioning
confidence: 97%
“…In addition, because TS symptoms in childhood vary with age, it was tested whether gene expression changes that occur with age in TS differ from normal control children. Whole blood was obtained from 30 children and adolescents with TS and 28 healthy children and adolescents matched for age, race, and gender (Lit, Enstrom, Sharp, & Gilbert, 2009). Gene expression (RNA) was assessed using whole-genome Affymetrix microarrays.…”
Section: Neurotransmitter-related Gene Expression Studies Of Bloodmentioning
confidence: 99%
“…A summary of these abnormalities, involving both innate and adaptive immune responses, is provided in Table 2 and Figure 2. Dysfunctional innate responses are supported by gene expression profiling of peripheral lymphocytes,76,77 and by measurements of monocyte-derived cytokines 78. Innate immunity dysfunction might cause incomplete elimination of pathogens with subsequent chronic immune-inflammatory activity: this is supported by the markedly raised antibody response to GABHS,69,70 Chlamydia trachomatis , and Toxoplasma gondii 79.…”
Section: What Is the Role Of Infections And Immunity In Chronic Tic Dmentioning
confidence: 99%